PENINGKATAN HASIL BELAJAR MURID PADA PEMBELAJARAN IPAS MELALUI PENERAPAN PBL BERBANTUAN MEDIA POWTOON DI KELAS III SDN 19 SANTUR KOTA SAWAHLUNTO - Affi Fatu Rahmi; Ranti Meizatri; Leni Zahara; Aissy Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of third-grade students in Natural and Social Sciences (IPAS) at SDN 19 Santur, Sawahlunto City. The problem was attributed to teacher-centered learning, limited student participation, and the suboptimal use of innovative learning models and instructional media. This study aimed to describe the improvement of students’ learning outcomes in IPAS through the implementation of the Problem Based Learning (PBL) model assisted by Powtoon media. This research employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The study was conducted in two cycles, consisting of two meetings in Cycle I and one meeting in Cycle II. Each cycle included four stages: planning, implementation, observation, and reflection. The research subjects were one teacher and 20 third-grade students of SDN 19 Santur, comprising 11 male students and 9 female students. The results showed continuous improvement in the quality of the teaching modules, increasing from 83.33% (Good) in Cycle I Meeting 1 to 87.50% (Good) in Cycle I Meeting 2 and 95.83% (Very Good) in Cycle II. Teacher activity scores improved from 78.57% (Good) to 85.71% (Good) and reached 96.42% (Very Good) in Cycle II. Similarly, student activity scores increased from 78.57% (Good) to 85.71% (Good) and 96.42% (Very Good). Students’ learning outcomes also improved, with the average score increasing from 69.31 in Cycle I Meeting 1 to 76.99 in Cycle I Meeting 2 and reaching 87.66 in Cycle II. Therefore, it can be concluded that the implementation of the Problem Based Learning (PBL) model assisted by Powtoon media effectively improved the IPAS learning outcomes of third-grade students.